A Textual Analysis of Newspapers, Madness, and the Lakeshore Psychiatric Hospital - Jackson, Kevin (Critical Disability Discourses, 2017)
Since the development of news media in North America, representations of mental illness have been a preeminent feature of news stories. These representations are key to understanding the intricacies of Mad people’s history, their marginalization, and their disenfranchisement. This paper provides asylum researchers with a simple yet effective strategy for examining how Mad people were portrayed in the Canadian asylum era by applying a qualitative textual analysis method to examine newspapers’ negative representations of “mad people” who were inmates at the Lakeshore Psychiatric Hospital in Etobicoke, Ontario. Drawing themes from a cross-section of relevant newspaper stories, this paper identifies the ways in which Mad people were –and continue to be – projected and perceived and how that has – or has not – changed over time. As a result, findings work to counteract many damaging and false perspectives adopted by newspapers and challenge the common belief that Mad people are inherently dangerous and thus deserving of incarceration. Keywords: Lakeshore Psychiatric Hospital; Mimico Asylum; Mad history; news media; post-structural textual analysis Une analyse textuelle des journaux, de la folie et l'hôpital psychiatrique Lakeshore Résumé Depuis le développement des médias d'information en Amérique du Nord, les représentations de la maladie mentale ont été une caractéristique prééminente des nouvelles. Ces représentations sont essentielles pour souligner les subtilités de l'histoire des Fous, leur marginalisation et leur privation de droits. Cet article offre aux chercheurs en droit d'asile une stratégie simple mais efficace pour examiner comment les gens fous ont été dépeints dans l'ère de l'asile au Canada en appliquant une méthode d'analyse textuelle qualitative pour examiner la représentation négative des «fous» par les journaux (Personnes ayant reçu un diagnostic de maladie mentale - avec ou sans garantie) qui étaient détenus à l'hôpital psychiatrique Lakeshore, à Etobicoke (Ontario). Tirant des thèmes d'une section transversale d'articles de journaux pertinents, cet article identifie les manières dont les personnes folles ont été - et continuent d'être - projetées et perçues et comment cela a changé - ou n’a pas changé - au fil du temps. Par conséquent, les conclusions permettent de contrecarrer de nombreuses perspectives préjudiciables et fausses adoptées par les journaux et de contester la croyance populaire selon laquelle les personnes folles sont intrinsèquement dangereuses et méritent donc d'être incarcérées. Mots clefs Hôpital psychiatrique Lakeshore; Mimico Asylum; histoire folle; médias; analyse textuelle post-structurelle